2011
DOI: 10.4161/hv.7.0.14607
|View full text |Cite
|
Sign up to set email alerts
|

Burden of the 1999-2008 seasonal influenza epidemics in Italy: Comparison with the H1N1v (A/California/07/09) pandemic

Abstract: Despite preventive efforts, seasonal influenza epidemics are responsible for substantial morbidity and mortality every year worldwide, including developed countries. The A/H1N1v pandemic imposed a considerable healthcare and economic burden. In order to obtain an accurate estimate of the economic burden of influenza, and hence to guide policymakers effectively, systematic studies are necessary. To this end, data from epidemiological surveillance are essential. To estimate the impact of the 1999-2008 seasonal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 12 publications
1
31
0
4
Order By: Relevance
“…In a study preformed in England, 779,000–1,164,000 general practice consultations, 19,000–31,200 hospital admissions, and 18,500–24,800 deaths annually were estimated to be attributable to influenza virus infections [18]. In the study performed in Italy, the estimated costs of seasonal epidemics from 1999–2008 in Italy ranged from EUR €15 to EUR €20 billion [19]. Differences in research methods, population and health care system including medical insurance system may have caused the difference of seasonal influenza disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…In a study preformed in England, 779,000–1,164,000 general practice consultations, 19,000–31,200 hospital admissions, and 18,500–24,800 deaths annually were estimated to be attributable to influenza virus infections [18]. In the study performed in Italy, the estimated costs of seasonal epidemics from 1999–2008 in Italy ranged from EUR €15 to EUR €20 billion [19]. Differences in research methods, population and health care system including medical insurance system may have caused the difference of seasonal influenza disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a meta‐regression analysis by Jayasundara et al has shown that the natural attack rate is about four times higher (15.2% vs 3.5%) in children than in adults. Our previous research documented that, in ten consecutive seasons, children aged 0‐14 years had the highest cumulative incidence of influenza‐like illness (ILI), followed by 15‐ to 64‐year‐olds, while the lowest cumulative incidence was constantly reported in the elderly. On the other hand, despite the lower incidence rates, influenza‐attributable hospitalizations and mortality are highest among the elderly; on average, about 90% of influenza‐related deaths occur in people aged 65 years or older …”
Section: Introductionmentioning
confidence: 99%
“…In the United States, more than 200,000 hospitalizations per year for respiratory and heart conditions have been attributed to seasonal influenza [2]. In Italy, considering seasonal epidemic periods alone, it has been estimated that 25 million cases of Influenza-like Illness (ILI) occurred from 1999 to 2008, with an average of 2.5 million cases per year [3]. …”
Section: Introductionmentioning
confidence: 99%